Characteristics and Outcomes of Patients with Primary Central Nervous System Lymphoma (Global Journal of Medical Research, 2017)
Background: The aim of the present retrospective study was to review the clinicopathological characteristics and outcomes of primary central nervous system lymphoma (PCNSL) cases at our institute. Methods: Patients diagnosed with PCNSL at our institute from August 2010 to May 2015 were evaluated. During the said period, a total of 14 cases were diagnosed with PCNSL. Results: Deep frontal lobe was the most common site of involvement while diffuse large B-cell lymphoma (DLBCL) was the most common histological pattern. 10 patients were treated with 3.0 g/m 2 methotrexate (MTX) intravenously concomitant with intraventricular 15 mg MTX and 2 patients were treated with radiotherapy (RT). Two of the patients died due to respiratory failure a short time after the treatment started. The median overall survival (OS) was 8 months (minimum: 1 months, maximum: 15 months) and the median OS was 12.42±13.20 months (min: 1 month, max: 48 months). Conclusion: As stated in the previous studies, MTX-based chemotherapy regimens are still the most effective treatment option in this patient population.
Keywords: methotrexate; overall survival; primary central nervous system lymphoma; radiotherapy